Monocyte-to-Lymphocyte Ratio is Associated with Depression 3 Months After Stroke - Ding K (Dove Medical Press, 2021)
Kai-qi Ding,* Ze-hua Lai,* Yu Zhang, Guo-yuan Yang, Ji-rong He, Li-li Zeng Department of Neurology and Institute of Neurology, Ruijin Hospital/Luwan Branch, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Li-li Zeng No. 197 Ruijin Second Road, Huangpu District, Shanghai, 200025, People’s Republic of ChinaTel +86-13816290607Email llzeng@126.comJi-rong He No. 149 Chongqing South Road, Huangpu District, Shanghai, People’s Republic of ChinaTel +86-13162762045Email kyo3shao@aliyun.comPurpose: To explore the relationship between the monocyte-to-lymphocyte ratio (MLR) and depression three months after acute ischemic stroke.Patients and Methods: From May 2013 to September 2014, 203 patients with acute ischemic stroke were recruited within 7 days post-stroke from Shanghai Ruijin Hospital and blood samples were collected after admission. The Hamilton Depression Scale and Clinical Review were evaluated at 3 months after stroke. Based on the Diagnostic and Statistical Manual of Mental Disorders-IV diagnostic criteria, we divided patients into post-stroke depression (PSD) and non-PSD groups. We analyzed the intergroup difference in MLR and the contributing factors. Moreover, dynamic changes in monocytes, lymphocytes and MLR at four different time intervals for all the stroke patients and their relationship with PSD patients were also studied.Results: The NIHSS scores and MLR in the PSD group were significantly higher than in the non-PSD group (p< 0.05). Logistic regression analysis revealed MLR was an independent risk factor for PSD (odds ratio: 18.020, 95% confidence interval: 1.127‒288.195, p=0.041). MLR correlated negatively with cholesterol and low-density lipoprotein (r=− 0.160 and − 0.165, respectively, p< 0.05). Within 7 days post-acute ischemic stroke, monocytes gradually increased while lymphocytes remained unchanged for all the stroke patients. The MLR value was significantly higher in the PSD group than in the non-PSD group within 24 h post-stroke (p< 0.05), but there was no difference in the other three time-intervals between the two groups.Conclusion: The admission MLR, particularly within 24 h post-stroke, was associated with PSD at 3 months, implying that the MLR might be involved in the PSD inflammatory mechanism.Keywords: MLR, depression, inflammation, acute ischemic stroke